Initial fitness, maturity status, and total training explain small and inconsistent proportions of the variance in physical development of adolescent footballers across one season - King, M.; Ball, D.; Weston, M.; McCunn, R.; Gibson, N. (Research in Sports Medicine, 2022)
To investigate how initial fitness, maturity status, and training time explain changes in physical performance across one season. Eighty-eight adolescent male footballers, representing four age categories (Under 15 [n=12], Under 14 [n=21], Under 13 [n=25], Under 12 [n=30]), were tested using physical performance tests (20 m sprint, change of direction, squat jump and yo-yo intermittent recovery test level 1 [YYIRTL1]) and maturity offset at the season start (Test 1) and end (Test 2). Multiple regression determined the proportion of variance in test score changes, explained by three predictor variables: initial fitness (i.e., Test 1), maturity offset change, and training time. With combined categories, predictor variables explained 0.051 to 0.297 of the variance in physical performance score changes. Analysing age categories separately, predictor variables explained 0.047 to 0.407 (20 m sprint), 0.202 to 0.626 (change of direction), 0.336 to 0.502 (squat jump), and 0.196 to 0.777 (YYIRTL1) of variance in test score changes. Of the limited differences in relative predictor contribution, Test 1 was the strongest predictor of test score change. Initial fitness, maturity status change, and training time explain small and inconsistent proportions of variance in adolescent footballers` physical development across one season.